Inverse Agonist Activity of Sarpogrelate, a Selective 5-HT2A-Receptor Antagonist, at the Constitutively Active Human 5-HT2A Receptor - Habib Abul Muntasir; Mohiuddin Ahmed Bhuiyan; Masaji Ishiguro; Masanobu Ozaki; Takafumi Nagatomo (Journal of Pharmacological Sciences, 2006)
Mutations producing constitutively active G-protein coupled receptors have been found in the pathophysiology of several diseases, implying that inverse agonists at the constitutively active receptors may have preferred therapeutic applications. Because of the involvement of 5-HT2A receptors in mediating many cardiovascular diseases, constitutively active mutants of the 5-HT2A receptor may be responsible for the disease states. Thus, the purpose of the present study was to investigate the inverse agonist activity of sarpogrelate, a selective 5-HT2A-receptor antagonist, and its active metabolite, M-1; and we compared their activities with those of other 5-HT2A-receptor antagonists such as ritanserin, ketanserin, and cyproheptadine. Using a constitutively active mutant (C322K) of the human 5-HT2A receptor, we demonstrated that like other 5-HT2A-receptor antagonists, sarpogrelate acts as a potent inverse agonist by significantly reducing basal inositol phosphate levels. However, there were no significant differences between sarpogrelate and other 5-HT2A-receptor antagonists for their inverse agonist activity. Compared with the wild type receptor, mutant receptor displayed significantly higher affinity for 5-HT and lower affinity for sarpogrelate. These results indicate that stabilization of the inactive conformation of the 5-HT2A receptor may be a key component of the mechanism of action of sarpogrelate. Keywords:: 5-HT2A receptor, sarpogrelate, mutant, constitutive activity, inverse agonist